FT Modulates Genome-Wide DNA-Binding of the bZIP Transcription Factor FD. Issue 1 (15th February 2019) - Collani, Silvio; Neumann, Manuela; Yant, Levi; Schmid, Markus
Abstract : Genomic and biochemical analyses identify targets of the flowering time regulator FD at the genome-wide scale and shed light on the requirement for interaction with the florigen FLOWERING LOCUS T. Abstract: The transition to flowering is a crucial step in the plant life cycle that is controlled by multiple endogenous and environmental cues, including hormones, sugars, temperature, and photoperiod. Permissive photoperiod induces the expression of FLOWERING LOCUS T ( FT ) in the phloem companion cells of leaves. The FT protein then acts as a florigen that is transported to the shoot apical meristem, where it physically interacts with the Basic Leucine Zipper Domain transcription factor FD and 14-3-3 proteins. However, despite the importance of FD in promoting flowering, its direct transcriptional targets are largely unknown. Here, we combined chromatin immunoprecipitation sequencing and RNA sequencing to identify targets of FD at the genome scale and assessed the contribution of FT to DNA binding. We further investigated the ability of FD to form protein complexes with FT and TERMINAL FLOWER1 through interaction with 14-3-3 proteins. Importantly, we observed direct binding of FD to targets involved in several aspects of plant development. These target genes were previously unknown to be directly related to the regulation of flowering time. Our results confirm FD as a central regulator of floral transition at the shoot meristem and provide evidence for crosstalk between the regulation of flowering and other signaling pathways, such as pathways involved in hormone signaling.